Student perceptions of the use of OneNote to create a capstone project in a teacher education program - Pena, Carmen (International Journal of Educational Technology and Learning, 2025)
During the Fall 2023 semester, a group of students in their first semester of the elementary education program at The University of Texas Rio Grande Valley (UTRGV) was required to use OneNote to complete a Community Case Study, which is a capstone project in the teacher education program at UTRGV. The project consists of three sections, which include a study of the school and district, visits to area attractions in the community, interviews with members of the community, and a final reflection on the project. The Community Case Study includes text-based files, graphics, and video. The authors used OneNote to have students document the various parts of the case study. The advantage of OneNote is that it allows students to upload all parts of the case study in one cohesive location as it accommodates text, graphics, and video. At the end of the semester, the authors had students fill out a student perception survey. This study discusses student perceptions of OneNote, the advantages of using OneNote, and the effects on project quality.